Home childbirth among young mothers aged 15–24 years in Nigeria: a national population-based cross-sectional study - Adewuyi, Emmanuel; Khanal, Vishnu; Zhao, Yun; David, Lungcit; Bamidele, Olasunkanmi David; Auta, Asa (BMJ PUBLISHING GROUP, 2019)
Objective To estimate the prevalence and identify factors associated with home childbirth (delivery) among young mothers aged 15-24 years in Nigeria. Design A secondary analysis of cross-sectional data from the 2013 Nigeria Demographic and Health Survey (NDHS). Setting Nigeria. Participants A total of 7543 young mothers aged 15-24 years. Outcome measure Place of delivery. Results The prevalence of home delivery among young mothers aged 15-24 years was 69.5% (95% CI 67.1% to 71.8%) in Nigeria - 78.9% (95%CI 76.3% to 81.2%) in rural and 43.9% (95%CI 38.5% to 49.5%, p<0.001) in urban Nigeria. Using the Andersen's behavioural model, increased odds of home delivery were associated with the two environmental factors: rural residence (adjusted OR, AOR: 1.39, 95% CI 1.06 to 1.85) and regions of residence (North-East: AOR: 1.97, 95% CI 1.14 to 3.34; North-West: AOR: 2.94, 95% CI 1.80 to 4.83; and South-South: AOR: 3.81, 95% CI 2.38 to 6.06). Three of the enabling factors (lack of health insurance: AOR: 2.34, 95% CI 1.16 to 4.71; difficulty with distance to healthcare facilities: AOR: 1.48, 95% CI 1.15 to 1.88; and <4 times antenatal attendance: AOR: 3.80, 95% CI 3.00 to 4.85) similarly increased the odds of home delivery. Lastly, six predisposing factors - lack of maternal and husband's education, poor wealth index, Islamic religion, high parity and low frequency of listening to radio - were associated with increased odds of home delivery. Conclusions Young mothers aged 15-24 years had a higher prevalence of home delivery than the national average for all women of reproductive age in Nigeria. Priority attention is required for young mothers in poor households, rural areas, North-East, North-West and South-South regions. Faith-based interventions, a youth-oriented antenatal care package, education of girls and access to health insurance coverage are recommended to speed up the reduction of home delivery among young mothers in Nigeria.